Avaliação de extratos de Phyllanthus acuminatus Vahl utilizada tradicionalmente como ictiotóxica na mortalidade de larvas de Aedes aegypti Linnaeus (Diptera: Culicidae) - Andrade, Juliana Nascimento (2013)
Dengue is an endemic disease caused by Aedes aegypti Linnaeus that besides have caused major epidemics in recent years in Brazil, does not have an effective vaccine. The larvae of these mosquitoes demonstrates high resistance to chemical larvicides commonly used in vector control activities and therefore some plants ictiotóxicas studies are targets for discovery of promising substances present in plant extracts that can be leveraged or even transformed into natural insecticides. This work began with an ethnobiological study conducted in the municipality of Maragogipe by using open and semi-structured interviews with local residents in order to collect information in different sociocultural levels, focusing on which plant is commonly used as ichthyotoxic, and then with possible larvicidal effect. Outo of the ichthyotoxic plants recorded, the species most cited was Phyllanthus acuminatus Vahl. The crude extract of the leaf and stem of this plant, as well as their different concentrations were tested in larvae of the mosquito A. aegypti checking the mortality rate at 24 and 48 hours at laboratory conditions to 25ºC in a growth chamber to assess its action as biopesticide agent. Although not standardized a suitable dosage of a larvicide from natural plant extracts tested, it was found that in higher concentrations it is possible to achieve the desired effect contributing to breaking the cycle of development of dengue vector and contributing to the reduction the indiscriminate use of synthetic larvicides that have high power toxicity.